Case Findings: Sodium Ferric Gluconate Complex and Fetal Bradycardia - Yang Pan; Jiayi Wang; Madeline Droney; Samuel Scovell; Joanne Hatfield; Erin Pender (Maternal-Fetal Medicine)
Abstract. Anemia in pregnancy is a significant event that often requires treatment to prevent long term effects in the mother and the fetus. Many factors determine which iron preparation to use, including route and ease of administration, patient tolerability, safety, and cost. This case report summarizes two separate patient cases where sodium ferric gluconate complex was administered intravenously to pregnant women, resulting in fetal bradycardia and emergent cesarean procedures.